Analysis of Customer Preferences and Willingness to Pay for Healthy Salad in Malang, Indonesia - Purba, Pebli Adenesli; Asmara, Rosihan; Andriani, Dwi Retno (Universitas Panji Sakti, 2025)
The growing trend of healthier eating habits, driven by increasing health awareness, presents a business opportunity for SMEs in the healthy food sector. This study investigates consumer preferences, attribute importance, and willingness to pay for vegetable salads in Malang, using a discrete choice experiment with a conditional logit model. A survey of 150 respondents who had purchased and consumed vegetable salads was conducted, analyzing key attributes, including health, mood, convenience, sensory appeal, natural content, and price, adapted from the food choice questionnaire and processed using R-Studio software. The findings indicate that consumers prefer vegetable salads that are high in fiber, free of additives, available in nearby shops, relaxing when consumed, and have a good taste. The ranking of attributes is important in purchasing decisions, as it follows the order of health, natural content, convenience, mood, and sensory appeal. Consumers' willingness to pay shows that they are willing to pay IDR 10,416 for